2015
DOI: 10.1016/j.asjsur.2014.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term results of harmonic scalpel hemorrhoidectomy versus stapler hemorrhoidopexy in treatment of hemorrhoidal disease

Abstract: HSH and SH are both safe and effective methods for surgical treatment of Grade III and Grade IV hemorrhoidal disease. In our study, the HSH method was determined to be safer, easier, and faster to perform, and associated with fewer long-term recurrences than the SH method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Twenty-nine and 9 articles [36][37][38][39][40][41][42][43][44] were selected for the chronological categories of 1998-2008 and 2009-2019, respectively. The mean number of patients per study was 197 ± 80 (range 22-3000 patients).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-nine and 9 articles [36][37][38][39][40][41][42][43][44] were selected for the chronological categories of 1998-2008 and 2009-2019, respectively. The mean number of patients per study was 197 ± 80 (range 22-3000 patients).…”
Section: Resultsmentioning
confidence: 99%
“…SH was introduced in 1998 as a conceptually attractive surgical technique as it mobilizes the prolapsed rectal mucosa above the dentate line, back to its original anatomical position [48]. Since stapling is meant to be performed above the dentate line on insensate rectal mucosa, postoperative pain and discomfort ought to be minimized, thereby positively influencing length of stay [42]. Resection of a circumferential ring of rectal mucosa eliminates all distal feeding vessels from the superior rectal artery, theoretically attaining a higher degree of surgical completeness and an expected lower risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…The operative time, duration of hospital stay, VAS scores, and analgesic doses showed no statistically significant differences between the two groups. Postoperative hemorrhage is a relatively common complication in SH, occurring in 1.5-15.6% of the patients [18][19][20][21] , and the maximum bleeding occurs immediately after surgery due to inadequate hemostasis. In SH, the closed staple height that determines the compression is 0.75 mm in PPH stapler and 1.5 mm in DST stapler.…”
Section: Discussionmentioning
confidence: 99%
“…However, none has proven to be clearly superior to the others. [ 20 24 ] SH and THD were described as more effective and less painful alternatives to CH. [ 25 , 26 ] A retrospective study indicated that both SH and THD are safe procedures and have similar effectiveness for treating grade III hemorrhoids.…”
Section: Discussionmentioning
confidence: 99%